2005
DOI: 10.1371/journal.pbio.0030159
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Switch in the Response of DRG Neurons to ETS Transcription Factor Signaling

Abstract: Two ETS transcription factors of the Pea3 subfamily are induced in subpopulations of dorsal root ganglion (DRG) sensory and spinal motor neurons by target-derived factors. Their expression controls late aspects of neuronal differentiation such as target invasion and branching. Here, we show that the late onset of ETS gene expression is an essential requirement for normal sensory neuron differentiation. We provide genetic evidence in the mouse that precocious ETS expression in DRG sensory neurons perturbs axona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
1,020
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,040 publications
(1,032 citation statements)
references
References 48 publications
(88 reference statements)
12
1,020
0
Order By: Relevance
“…10 VGATChR2-EYFP mice (Jackson laboratory, JAX Stock#014548) and 9 PV-ires-cre 44 crossed to Rosa26-LSL-ReaChR, red-shifted channel rhodopsin reporter mice (JAX 24846) 45 , were used for photoinhibition behavior experiments. A subset of these mice (5 VGAT-ChR2-EYFP mice, 7 PV × ReaChR mice) were used for simultaneous electrophysiology and behavior.…”
Section: Micementioning
confidence: 99%
“…10 VGATChR2-EYFP mice (Jackson laboratory, JAX Stock#014548) and 9 PV-ires-cre 44 crossed to Rosa26-LSL-ReaChR, red-shifted channel rhodopsin reporter mice (JAX 24846) 45 , were used for photoinhibition behavior experiments. A subset of these mice (5 VGAT-ChR2-EYFP mice, 7 PV × ReaChR mice) were used for simultaneous electrophysiology and behavior.…”
Section: Micementioning
confidence: 99%
“…Striatal ACh and FS acquire their phenotype during the first 2–3 postnatal weeks in rodents along with the expression of specific markers such as choline acetyltransferase (ChAT, Ach; Phelps, Brady, & Vaughn, 1989) and parvalbumin (PV, FS; Schlösser, Klausa, Prime, & Bruggencate, 1999). To conditionally delete Smo in ACh or FS, we selected the ChAT‐Cre (Rossi et al, 2011) and PV‐Cre (Hippenmeyer et al, 2005) lines (Figure 2a,e). To validate the specificity of these mouse lines, we used the Rosa26R‐YFP reporter mouse.…”
Section: Resultsmentioning
confidence: 99%
“…All experiments were performed according to institutional guidelines approved by the ethics committee of the Hospital Universitario Virgen del Rocio and the European Community (Council Directive 86/609/EEC). Pv Cre (Hippenmeyer et al, 2005), Chat Cre (Rossi et al, 2011), Smo Flox (Long, Zhang, Karp, Yang, & McMahon, 2001), Shh Flox (Lewis et al, 2001), Rosa26R‐Tomato (Madisen et al, 2010), and Rosa26R‐YFP mice (Srinivas et al, 2001) were obtained from Jackson Laboratory (Stocks numbers 8,069, 6,410, 4,526, 4,293, 7,909, and 6,148) and were maintained on their genetic background (B6;129P2, C57BL/6, 129X1/SvJ, and C57BL/6J). Breeding previous lines, we generated Pv Cre/+ ; Smo loxP/loxP (PV‐Smo), Chat Cre/+ ; Smo loxP/loxP (ChAT‐Smo), Pv Cre/+ ; Shh loxP/loxP (PV‐Shh), and Chat Cre/+ ; Shh loxP/loxP (ChAT‐Shh).…”
Section: Methodsmentioning
confidence: 99%
“…Motor neuron phenotypes normally arise through the precisely timed sequential activation of transcriptional networks (reviewed in Shirasaki and Pfaff, 2002). It has been suggested that the strategy of requiring target-derived signals to induce late-acting regulatory factors, such as ER81 and PEA3, is an effective way of coordinating neuronal differentiation with target maturation, thereby ensuring the orderly temporal sequence of transcription factor expression that is required for neural maturation and circuit assembly (Livet et al, 2002;Hippenmeyer et al, 2005). Indeed, premature activation of Er81 signaling in sensory neurons has severe consequences; sensory axons fail to project into spinal cord, induce fewer muscle spindles, branch less extensively in skin, and survive independently of neurotrophic factors (Hippenmeyer et al, 2005).…”
Section: Timing Of Expressionmentioning
confidence: 99%
“…Other characteristics, for example expression of the ETS transcription factors ER81 and PEA3, ap-pear somewhat later in development after axons enter the limb, being triggered and refined by interactions with limb-derived signals (Lin et al, 1998;Price et al, 2002;Wang and Scott, 2004). The precise temporal activation of these transcriptional programs is essential for the normal maturation of both motor (reviewed in Shirasaki and Pfaff, 2002) and sensory neurons (Hippenmeyer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%